Extraction of Vanillin Through Hydrotropy - Dhinakaran, Masilamani; Bertie Morais, Antony; Nagendra Gandhi, Nagarajan (Asian Journal of Chemistry, 2012)
Natural vanillin (4-hydroxy-3-methoxybenzaldehyde) produced from vanilla beans and other naturals is one of the most common flavour chemicals widely used in a broad range of flavours. In present work,vanilla beans are permeabilized by aqueous hydrotrope solutions followed by extraction and solubilization of vanillin into the hydrotrope solutions of nicotinamide, sodium salicylate, resorcinol and citric acid. The influence of a wide range of hydrotrope concentrations (0-3.0 mol/L) and different system temperatures (303-333 K) on the solubility of vanillin has been studied. The solubility of vanillin increases with increase in hydrotrope concentration and also with system temperature and nicotinamide were found to be effective for the selective extraction of vanillin with a recovery of 85 % from the aqueous solution of hydrotropes with high purity. The process was further optimized with respect to concentration of hydrotropes and temperature of extraction. A minimum hydrotrope concentration was found essential to show a significant increase in the solubility for vanillin + water system. Consequent to the increase in the solubility of vanillin, the mass transfer coefficient was also found to increase with increase in hydrotrope concentration at 303 K. The enhancement factor, which is the ratio of the value in the presence and absence of a hydrotrope, is reported for both solubility and mass transfer coefficient of vanillin. The Setschenow constant, Ks, a measure of the effectiveness of a hydrotrope, was determined for each case.